All-MBE grown InAs/GaAs quantum dot lasers with thin Ge buffer layer on Si substrates. (22nd October 2020) - Yang, Junjie; Liu, Zizhuo; Jurczak, Pamela; Tang, Mingchu; Li, Keshuang; Pan, Shujie; Sanchez, Ana; Beanland, Richard; Zhang, Jin-Chuan; Wang, Huan; Liu, Fengqi; Li, Zhibo; et al.
Abstract: A high-performance III–V quantum-dot (QD) laser monolithically grown on Si is one of the most promising candidates for commercially viable Si-based lasers. Great efforts have been made to overcome the challenges due to the heteroepitaxial growth, including threading dislocations and anti-phase boundaries, by growing a more than 2 µ m thick III–V buffer layer. However, this relatively thick III–V buffer layer causes the formation of thermal cracks in III–V epi-layers, and hence a low yield of Si-based optoelectronic devices. In this paper, we demonstrate a usage of thin Ge buffer layer to replace the initial part of GaAs buffer layer on Si to reduce the overall thickness of the structure, while maintaining a low density of defects in III–V layers and hence the performance of the InAs/GaAs QD laser. A very high operating temperature of 130 °C has been demonstrated for an InAs/GaAs QD laser by this approach.